Porous silicon antibody microarrays for quantitative analysis: measurement of free and total PSA in clinical plasma samples. - Järås, K; Adler, B; Tojo, A; Malm, J; Marko-Varga, G; Lilja, H; Laurell, T (2012)
The antibody microarrays have become widespread, but their use for quantitative analyses in clinical samples has not yet been established. We investigated an immunoassay based on nanoporous silicon antibody microarrays for quantification of total prostate-specific-antigen (PSA) in 80 clinical plasma samples, and provide quantitative data from a duplex microarray assay that simultaneously quantifies free and total PSA in plasma. To further develop the assay the porous silicon chips was placed into a standard 96-well microtiter plate for higher throughput analysis. The samples analyzed by this quantitative microarray were 80 plasma samples obtained from men undergoing clinical PSA testing (dynamic range: 0.14-44 ng/ml, LOD: 0.14 ng/ml). The second dataset, measuring free PSA (dynamic range: 0.40-74.9 ng/ml, LOD: 0.47 ng/ml) and total PSA (dynamic range: 0.87-295 ng/ml, LOD: 0.76 ng/ml), was also obtained from the clinical routine. The reference for the quantification was a commercially available assay, the ProStatus PSA Free/Total DELFIA. In an analysis of 80 plasma samples the microarray platform performs well across the range of total PSA levels. This assay might have the potential to substitute for the large-scale microtiter plate format in diagnostic applications. The duplex assay paves the way for a future quantitative multiplex assay, which analyzes several prostate cancer biomarkers simultaneously.